C1 esterase inhibitor mediated protection from acute lung injury - Hess, Rosanna Marie; Justus Liebig University Giessen (My University, 2016)
C1 esterase inhibitor (C1 INH) represents not only the sole inhibitor of the classic pathway of complement activation but also the main inhibitor of the contact system, irreversibly inactivating FXII and KLK by complex formation. The anti-inflammatory attributes of C1 INH have been detected to extend beyond its activity as serine protease inhibitor, including also the prevention of leukocyte migration by directly interacting with endothelial cells. This study contemplates the involvement of the intrinsic factors of blood coagulation in lung injury with particular focus on FXII, the initiator of the intrinsic cascade. Elevated levels of FXII, FXI, KLK and HK in the bronchoalveolar lavage fluids (BALF) and lung tissue of ARDS patients were observed with evidence of ongoing contact system activity. In consistency with these results for ARDS patients were the observations made in the animal model of lung injury; here correspondingly increased FXII levels in BALF and lung homogenate became evident after bleomycin application. Of pivotal interest for future therapeutic approaches is the here presented recognition of a favorable effect of C1 INH administration in lung injury. Thus, C1 INH application was shown to attenuate the inflammatory process in pulmonary tissue of bleomycin injured lungs, significantly reducing the number of inflammatory cells, particularly neutrophils and inducing a regression of the alveolar edema. Furthermore, administration of the inhibitor was followed by a significant decrease of tumor necrosis factor-alpha and macrophage inflammatory protein-2. In summary, the present study provides reason to assume an implication of the contact system factors in the inflammatory process of the ARDS, possibly by promoting the release of cytokines causing neutrophil derived lung tissue destruction. Furthermore, a protective effect of C1 INH in lung injury is described, pointing towards the anti-inflammatory properties of the serine protease inhibitor such as the inhibition of neutrophil recruitment to the sites of injury via binding of C1 INH to selectins. Therefore the investigation draws new attention to C1 INH as a potential future option in the therapy of inflammatory lung diseases such as ARDS.
Keywords: ddc:610